Foucault, Buddhism and disciplinary rules - Voyce, Malcolm (Routledge, Taylor & Francis Group, 2017)
Introduction to the work of Foucault and its use in this study -- An overview of the Vinaya -- The presentation of the Vinaya within forms of western scholarship -- The Vinaya and the Dharmasastra -- The formation of the religious body -- From ethics to aesthetics -- The role of confession and discipline -- Rules and transgressions -- The care of the self and the practice of the Vinaya